Nondestructive void size determination in copper metallization under passivation - Gan, Zhenghao (2009)
A novel nondestructive failure analysis technique to rapidly locate tiny voids in narrow metallization line covered with passivation is proposed, based on the simulation results. In this technique, the current alteration in a metal line under study is recorded continuously when it is subjected to electron beam shining and biased by a small external voltage. Finite-element analysis is performed to simulate the temperature distribution and current alteration in the metal line. The electron-beam heating is demonstrated as the most important factor contributing to the current alteration. Reconstruction of voids with any shape(such as wedge or slit) is possible on the basis of the gradient of the current alteration. It is found that the minimum detectable void size can be as low as 50 nm. Experimental verification of the technique is underway.